2015
DOI: 10.4155/fmc.15.148
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ubiquitination for Cancer Therapies

Abstract: Ubiquitination, the structured degradation and turnover of cellular proteins, is regulated by the ubiquitin-proteasome system. Most proteins that are critical for cellular regulations and functions are targets of the process. Ubiquitination is comprised of a sequence of three enzymatic steps, and aberrations in the pathway can lead to tumor development and progression as observed in many cancer types. Recent evidence indicates that targeting the ubiquitin-proteasome system is effective for certain cancer treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 148 publications
(163 reference statements)
0
83
0
1
Order By: Relevance
“…Ubiquitylation is also a highly versatile post-translational modification, and it can involve assemblies of eight distinct chain-linkage types (M1, K6, K11, K27, K29, K33, K48, and K63), wherein K11 and K48 contribute preferentially to proteasomal turnover. In keeping with such central roles in biology, components of the UB system are frequently mutated in disease (Ciechanover and Kwon, 2015; Morrow et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitylation is also a highly versatile post-translational modification, and it can involve assemblies of eight distinct chain-linkage types (M1, K6, K11, K27, K29, K33, K48, and K63), wherein K11 and K48 contribute preferentially to proteasomal turnover. In keeping with such central roles in biology, components of the UB system are frequently mutated in disease (Ciechanover and Kwon, 2015; Morrow et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As UPS regulates numerous aspects of cellular function, defects in this system may result in the pathogenesis of various significant human diseases, including tumors (19,20). Ubiquitin may be added to a substrate protein by the concerted action of ubiquitin-activating enzyme (E1), ubiquitin-conjugating enzyme (E2), and ubiquitin protein ligase (E3) (18).…”
Section: Discussionmentioning
confidence: 99%
“…As UPS regulates degradation of various types of protein, it is crucial in a variety of cellular processes. UPS aberrations have been observed in numerous types of human tumor (19,20). However, limited information is available regarding aberrations of CDC34 in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The proteomic studies have shown that all types of polyubiquitination co‐exist in cells 14, 15. Lys48‐linked chains are the most abundant linkage type (often > 50% of all linkages) found in cells that are primarily involved in transfer of substrate proteins to the 26S proteasome for degradation 16. However, K63‐linked polyubiquitination, the second most abundant form of ubiquitylation, has various non‐proteolytic roles in cells 8.…”
Section: Ubiquitin Modificationsmentioning
confidence: 99%
“…The mammalian genome encodes nearly 100 putative DUBs. DUBs are classified into 6 subfamilies according to the structure of their catalytic domain: Ub‐specific proteases (USPs), Ub C‐terminal hydrolases (UCHs), ovarian tumour‐like proteases (OTUs), JAB1/MPN/Mov34 metalloenzymes (JAMMs), Machado‐Jakob disease (MJD) proteases and a recently identified monocyte chemotactic protein‐induced protein (MCPIP) family 16, 26, 27, 28. This family of DUBs is activated depending on their specificity for the type of Ub chain conjugation attached to the substrate 28.…”
Section: Deubiquitylation Enzymesmentioning
confidence: 99%